STRATEGI KOMUNIKASI DI PESISIR PANTAI WISATA PELUANG DAN TANTANGAN BAGI WIRAUSAHAWAN BARU - Subekti, Priyo; Sjuchro, Dian Wardiana (JURNAL SIGNAL, 2024)
When starting and growing businesses, budding entrepreneurs in coastal tourism areas face various challenges and opportunities. Family and community support, access to social media, government cooperation, and cross-sector collaboration offer valuable resources but also introduce market and regulatory navigation complexities. To provide insights into effective strategies to encourage more involvement in entrepreneurship, focusing on integrating communication strategies in coastal tourism areas. A qualitative approach is used through case studies, with primary data collected from budding entrepreneurs in the coastal tourism sector through in-depth interviews, observations, and content analysis demonstrating the importance of building strong communication networks through stakeholder collaboration to help entrepreneurs overcome initial challenges and capitalise on opportunities. Establishing communication networks is critical for entrepreneurial success, with family and community support providing an essential foundation for business growth and development. Communication strategies developed by the government and relevant agencies should include elements that support the formation of these networks, ensure adequate socialisation, and provide complete and accurate information to new entrepreneurs to guide them through the entrepreneurial process. Key Words: budding entrepreneurs, tourist beach, social network, communication strategy, marketing strategy